Analisa Perfoma Jaringan Wifi Berbasis Smartphone Sebagai Tethering dan Smartphone Sebagai Modem dengan Metode Perbandingan - Purwono Hendradi; Mukhtar Hanafi; Humaid Husain As’ad (Journal of Information System Research (JOSH), 2023)
At this time smartphones sound familiar to the public. Smartphones are included in the auxiliary tools in the continuity of human life equipped with various features that have the same capabilities as computers, so it is no stranger to the ears of the community with it because it provides convenience for users. One of the features given to smartphones is the tathering feature, Tethering makes it easy for users to share internet connections in a way that is easy to use in every age group of society in general. This research uses an experimental method by analyzing two objects. Based on the test results, the test was carried out using the speed test application 10 times within 1 day and obtained an average on both objects that showed a comparison of the results obtained and showed the superiority of using a smartphone as a modem compared to a tethering smartphone. In this test, get the average value of the router download: 15.66 and upload: 18.207 then the average value of tethering download: 10,815 and upload: 16,271 from the beginning of the average network used download: 20.782 and upload: 20,51. With the average comparison above, it can be concluded that the use of a smartphone as a modem has a superior network sharing average using MBps as a measure.